Kualitas Pelayanan Pendidikan dan Kepuasan Lulusan Lembaga Kursus dan Pelatihan (LKP) Vision College - Sunarsih, Alfania; Suminar, Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
In the era of globalization, it requires institutions to manage in order to create quality human resources in accordance with existing demands. This study aims to determine the quality of educational services and graduate satisfaction of LKP Vision College. The research method is a qualitative approach to reveal educational services and graduate satisfaction with interactive model analysis. The results of this study indicate that the quality of educational services at LKP Vision College plays an important role in ensuring graduate satisfaction. A clear division of labor between each division in this institution supports the achievement of structured and quality educational goals. However, although LKP Vision College has provided quite complete facilities, there are some shortcomings that need to be considered to further improve service quality. The absence of a document shredder and some facilities that have not been optimized can reduce the comfort and professionalism of the institution.